Estudo das doenças cárie e periodontal em mulheres durante o período gestacional - Natalia Nogueira Coutinho (2006)
This prospective study aimed learn the oral health conditions of pregnant women enrolled in the Integrated Program of Womens Health Attention and evaluate the influence of clinical and socio-demographic factors on their oral health, and the effectiveness of primary oral care measures in caries and periodontal disease. Obtained ethical consent, 105 pregnant women were submitted to an interview concerned socio-demographic background, factors related to pregnancy (perceived of gingival bleeding and sickness) and oral hygiene habits. They were also examined, considering the parameters: visible plaque index (VPI); bleeding on probing (BP); probing depth (PD); clinical attachment level (CAL); presence of active white spot lesions (AWSL) and stimulated salivary flow rate (SF). From those, 67 pregnant women were followed-up until 3rd gestational trimester. Initially, they were classified, according the clinical diagnosis of active white spot lesions (AWSL), gingivitis and/or light to moderate periodontal disease (GLMPD), in: G1-absence of AWSL and GLMPD; G2-presence of AWSL; G3-presence of GLMPD; G4-presence of AWSL and GLMPD. Theyre submitted to control procedures including oral hygiene instructions, initial periodontal therapy (scaling and root planning) and topical fluoride; and revalued in the 2nd and 3rd gestational trimesters. When the clinical parameters were compared to socio-demographic and behaviors variables, only the relation between habit of using dental floss and bleeding on probing were statistically significant (p<0.05). VPI presented a significant correlation with caries activity (p<0.001), but stimulated salivary flow rate was not statistically related to caries activity. The changes in the parameters were appraised through Friedman test (=0,05). A significant reduction was observed in the periodontal parameters (p <0.001) and in the percentile of cases with AWSL (p<0.001), without significant difference of SF (p=0.622). The frequency of pregnant women classified as G1, G2, G3 and G4, at 1st and 3rd trimesters were, respectively: 23.9% and 53.7%; 1.5% and 6%; 44.7% and 37.3%; 29.9% and 3%.The implemented procedures were effective: they favored the reduction of numbers of pregnant women in G4 (presence of GLMPD and AWSL) and the increment in G1 (absence of GLMPD and AWSL).